2014
DOI: 10.1002/gcc.22224
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous DNA methylation contributes to tumorigenesis through inducing the loss of coexpression connectivity in colorectal cancer

Abstract: Increasing evidence indicates the high heterogeneity of cancer cells. Recent studies have revealed distinct subtypes of DNA methylation in colorectal cancer (CRC); however, the mechanism of heterogeneous methylation remains poorly understood. Gene expression is a natural, intermediate quantitative trait that bridges genotypic and phenotypic features. In this work, we studied the role of heterogeneous DNA methylation in tumorigenesis via gene expression analyses. Specifically, we integrated methylation and expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 46 publications
(74 reference statements)
0
11
0
Order By: Relevance
“…Nevertheless, a hypothesis that heterogeneous methylation may be a “passenger” that interferes with transcription processes has been proposed, 16 and heterogeneous methylation may play an important role in tumour development 25 through perturbing the transcriptome in CRC. 37 …”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, a hypothesis that heterogeneous methylation may be a “passenger” that interferes with transcription processes has been proposed, 16 and heterogeneous methylation may play an important role in tumour development 25 through perturbing the transcriptome in CRC. 37 …”
Section: Discussionmentioning
confidence: 99%
“…The methylation heterogeneity (intermediate methylation 1 or partially methylated domain 2 ) is reported in primordial germ cells under epigenetic reprogramming, 3 sperms, 4 embryonic stem cells, 5 induced pluripotent stem cells, 6 placental cells, 2 and other somatic cells under normal and disease conditions. [7][8][9] These regions are highly gene enriched and often interact with other epigenetic markers such as histone modifications. 1 In embryonic stem cells, allelic heterogeneity is involved in maintaining the bimodal states of gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…5 Furthermore, allelic heterogeneity is frequently found in various types of cancer cells, and the possible relationship with aberrant gene expression in cancer cells is of particular interest. 9 While previous studies have defined allelic heterogeneity based mainly on the methylation levels of individual CpG sites, the underlying methylation pattern within each allele has not yet been examined. Accordingly, it is important to determine the linear methylation pattern of consecutive CpG sites within each allele.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been reported that the methylation patterns present in several imprinted genes and repetitive elements of embryonic germ (EG) cells may exhibit DNA methylation changes occurring in the germ cell lineage during the differentiation process [32]. Induction of mosaic DNA methylation patterns also leads to tumorigenesis by participating in important cancer related pathways and thus causing loss of co-expression connectivity in colorectal cancer [33]. The presence of epigenetic heterogeneity of developmentally important genes has important implications for assisted reproduction outcomes [34].…”
Section: Discussionmentioning
confidence: 99%